Традиционные обереги хантов бассейна р. Тром-Аган (по материалам полевых исследований) - Starodubova, O. V.; Стародубова, О. В. (Издательство Тюменского государственного университета, 2016)
The article focuses on apotropaic traditions of the Khanty of the Tromyogan river. Based on the data of her field research, the author considered some items that are related to the categories of direct and indirect apotropes of various levels, like individual or family. Apotropes, that have only a sacred purpose and are aimed at human protection, health and prosperity of both the person and his or her family members, including descendants, are regarded as direct apotropes. Such items as umbilical cord of a newborn, bear fangs and claws, pieces of fir bark and Chaga mushroom are traditionally considered as objects that have such magic power. This category also includes types of decoration of some clothing items. The category of indirect apotropes includes things that have, first of all, utilitarian function: knife, whetstone, hearth, needle-case. According to the traditional worldview, these items are attributed to the certain Upper forces (like fire or metal), so they could be a powerful personal talisman. The hearth more and more revered as a manifestation of the Goddess of Fire, so that makes it to be a special sacral micro-space. По материалам полевых исследований рассматривается обрядовая деятельность хантов бассейна р. Тром-Аган.